Avaliação radiográficada fusão das corticias lateral e medial do ramo mandibular: estudo em mandíbulas secas - Klüppel, Leandro Eduardo; Cavalieri, Lucas Oliveira; Antonini, Fernando; Gonçalves, Marcelo [UNESP]; Bolini, Paulo Domingos André [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Pereira Filho, Valfrido Antonio [UNESP] (My University, 2012)
Purpose: to radiographically evaluate the distance between mandibular lingula and the exact spot where buccal and lingual cortical bone plates merge in the mandibular ramus. Materials and Methods: 54 dry mandibles, divided into 3 subgroups (SG1: dentate, SG2: partially dentate and SG3: edentulous) were used in this study. Lingula position was marked with a metallic sphere and radiographs were taken. The distance between mandibular notch and lingula (I/L) and the distance between mandibular lingula and cortical bone plates fusion (L/FC) were measured. Statistical analysis was applied to the values obtained. Results: mean values for L/FC were 8,18mm, 7,30mm and 8,98mm for SG1, SG2 e SG3 respectively. Moreover, mean values for I/L were 14,02mm, 13,90mm and 12,34mm for SG1, SG 2 and SG3 respectively. The results also showed that cortical bone plates fusion took place in half I/L distance in 28,57% of the mandibles in SG1, in 46,67% of the mandibles in SG2 and in 9,09% of the pieces in SG3. Conclusions: there were no statistically significant differences in the height where cortical bone plates took place in all 3 subgroups. In SG3, the correlation between the mean value for L/FC and the mean value for I/L suggests a reduction in bone density and bone mass, which can correlate to the evaluation of older mandibles in this subgroup.

Objetivo: Avaliar radiograficamente a distância da língula da mandíbula até o ponto onde ocorre a fusão das corticais ósseas vestibular e lingual no ramo mandibular. Materiais e Métodos: 54 mandíbulas secas, divididas em 3 subgrupos (SG1: dentada, SG2: parcialmente dentada e SG3: desdentada), foram utilizadas neste estudo. A posição da língula foi demarcada com esfera metálica, e tomadas radiográficas foram obtidas. As distâncias entre a incisura e a língula mandibular (I/L) e entre a língula mandibular e o ponto onde ocorre a fusão das corticais ósseas no ramo mandibular (L/FC) foram mensuradas. Análise estatística pertinente foi aplicada aos valores obtidos. Resultados: a média dos valores obtidos para L/FC foram de 8,18mm, 7,30mm e 8,98mm para SG1, SG2 e SG3, respectivamente. Entretanto, os valores de I/L foram de 14,02mm, 13,90mm e 12,34mm para SG1, SG 2 e SG3, respectivamente. Os resultados também demonstram que a fusão das corticais ocorreu na metade da distância I/L em 28,57% das mandíbulas em SG1, em 46,67% das mandíbulas em SG2 e em 9,09% das peças em SG3. Conclusões: não houve diferenças significativas nas alturas em que ocorreram as fusões nos 3 subgrupos. No SG3, a correlação do valor médio de L/FC com o valor médio observado para I/L (12,34 mm) sugere uma diminuição da densidade óssea e da massa óssea, que pode estar relacionada com uma idade avançada das mandíbulas avaliadas nesse subgrupo.
Keywords: Radiography; Mandible; Anatomy; Cirurgia Ortognática; Mandíbula; Ramo mandibular